In silico Molecular Docking and ADMET Study of Some Potential Antiviral Drug Candidates as Potential Inhibitors of SARS-CoV-2 Protease Mpro (6Y2F) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
In this present world COVID-19 pandemic is one of the biggest concern. An appealing medication focus among Covids is the fundamental protease; SARS-CoV-2 protease Mpro (6Y2F) due to its fundamental role in handling the polyproteins that are interpreted from the viral RNA. The present study showed the interaction of favipiravir, ganciclovir, raltegravir and remdesivir against 6Y2F, using molecular docking were analyzed. Among those ligands’ interaction with protein structure, 6Y2F on raltegravir (-7.4 kcal/mol) and remdesivir (-6.9 kcal/mol), respectively displayed maximum binding affinity. The interactions of four ligands were contrasted with each other in that ganciclovir and raltegravir form highest number of hydrogen bond with 6Y2F. The interacting amino acids residues (Gly143, Ser144, Cys145) were studied and all selected ligands were predicted to be non-carcinogens and non-AMES toxic.Dhaka Univ. J. Pharm. Sci. 20(2): 177-183, 2021 (December)